Clinical activity of alvocidib (flavopiridol) in acute myeloid leukemia. Issue 12 (December 2015) - Zeidner, Joshua F.; Karp, Judith E.
Highlights: Alvocidib has been studied in 405 AML patients in a timed sequential regimen (FLAM). Complete remission rates are 36% in relapsed and refractory AML. Complete remission rates are 68% in newly diagnosed, predominantly poor-risk, AML. Further investigation is ongoing to determine alvocidib's role in AML. Abstract: There have been minimal therapeutic advancements in acute myeloid leukemia (AML) over the past 4 decades and outcomes remain unsatisfactory. Alvocidib (formerly flavopiridol) is a multi-serine threonine cyclin-dependent kinase inhibitor with demonstrable in vitro and clinical activity in AML when combined in a timed sequential chemotherapy regimen, FLAM (alvocidib followed by cytarabine continuous infusion and mitoxantrone). FLAM has been evaluated in sequential phase 1 and phase 2 studies in 149 and 256 relapsed/refractory and newly diagnosed non-favorable risk AML patients, respectively, with encouraging findings in both patient populations warranting further investigation. This review highlights the mechanism of action of alvocidib, pre-clinical studies of alvocidib in AML, and the clinical trials evaluating alvocidib alone and in combination with cytotoxic agents (FLAM) in AML.